Find the sum of the real roots that satisfy the equation
x + 3 − 3 − x + x + 2 − 2 − x + x + 1 − 1 − x = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
After changing
x
to
−
x
and some algebraic manipulation, a same equation is formed.
This means that if
x
is a solution, so does
−
x
.
The sum
=
0
@Otto Bretscher oh my god! you got another account? =D =D
The equation above is equivalent to x + 3 + 3 − x x + x + 2 + 2 − x x + x + 1 + 1 − x x = 0 x ( x + 3 + 3 − x 1 + x + 2 + 2 − x 1 + x + 1 + 1 − x 1 ) = 0 Since x + 3 + 3 − x 1 + x + 2 + 2 − x 1 + x + 1 + 1 − x 1 > 0 ; ∀ x ∈ [ − 1 ; 1 ] so the only solution is x = 0
Your solution is my favorite solution of the three. Great job!
Problem Loading...
Note Loading...
Set Loading...
It is easy to see that x = 0 satisfy the equation. To prove that this is unique, the equation...
x + 3 − 3 − x + x + 2 − 2 − x + x + 1 − 1 − x = 0
implies x + 3 + x + 2 + x + 1 = 3 − x + 2 − x + 1 − x
Noticed that the LHS and RHS are both one-to-one and LHS is increasing while RHS is decreasing. Thus, the equation has at most 1 solution. Therefore, the sum of the roots is 0 .